A formação do corpo policial na Província de Mato Grosso no século XIX (1831-1858) - Martins, David Campos (2013)
This thesis revolves around the formation of the Police Corps in the province of Mato Grosso around the year 1831 to 1858, and seeks to understand how the police institution influenced the formation of urbanity and civility in Mato Grosso, especially in the provincial capital. Contextualization are addressed in the conditions that existed prior to reaching the devices of society in the nineteenth century. In reading performed showed that the Police Corps has emerged as a function of the maintenance of order and the construction of a possible urbanity. Reading between the lines it is clear there is a need to institutionalize this newly formed Corps Officer, ie, the craft of policing effected only in the province of Mato Grosso from the first half of the century. The dissertation also shows how agents emerged was that maintainers of order, and which individuals played police functions. A membership weakened and differentiated in relation to the court, these agents were recruited incorporated, and through a forceful way, these agents have become maintainers of individual interests, and the interests defended were the King and the elite, and not the body collective society as disclosed. The Police Corps established directly by the company presents its own social characteristics, being directly linked to the site, once the Police of the Province of Mato Grosso, in the nineteenth century was unique and consisted of characteristics of society itself.